NET.OS : Network Server Operating Systems Based on Open Source - Evan Enza Rizqi; Idhawati Hestingsih; Mardiyono Mardiyono (IAES Indonesia Section, 2015)
Open source server operating system mostly still usestext-based user interface and it makes hard to learn to new userin Vocational High School of Computer Network Department.This problem will be dealt by providing Graphical User Interface(GUI) in the server operating system accompany Command LineInterface feature. This paper describes the development of opensource server operating system which provides serverconfiguration in text mode and graphics mode. This researchmethod involves the study of literature and the development ofoperating systems with remastering concept including selectingfeatures, selecting graphics display, selecting the basic system,remastering, and testing to the Server PC. Research productcalled Net.OS (Network Technology Server OS) was tested incomputer networks to validate the server functions. The resultsshow that all functions can work successfully. Net.OSimplementation can provide a user friendly to configure theserver in a web-based graphical mode, text mode, moreover itbecomes a bridge of Linux newbie to learn the serverconfiguration using GUI.